An Overview of Educational Computing. - Willis, Jerry (Education Digest, 1984)
Focuses on educational computing. View that the current shift to an information-oriented society is reason enough to introduce computers as a universal topic of study in schools today; Focus on helping students overcome their hesitations about computers and become computer-literate is a more important goal than offering programming courses to a few students; Increase in computer usability throughout schools in the U.S.